Recognition of architectural patterns in the houses of the Niakie neighborhood in Amol - Sanaei, Zohreh; Mirhadi, Jamshid; Asgharzadeh, Ali (Revista de la Universidad del Zulia, 2020)
Traditional housing fabrics are an obviously valuable heritage to be reviewed and analyzed, as they present the right pattern for native architecture because it is considered the main core in the creation of cities, as well as the architectural elements and buildings located in them. The objective of this study is to review and recognize the physical and social behavior patterns of these buildings to improve these valuable fabrics and save them from their presence of unusual buildings. First, this study would review the key problems on the design of patterns in the architecture of the house, obtaining an analytical-descriptive point of view; This research first reviews the key issues of the patterns in the architecture of the house, and then identifies the physical components that are effective in traditional buildings, contrasting with the theoretical foundations obtained. The next step has been the identification and physical review using the field research method to physically identify and review the case study buildings in the historical fabric. After the analysis, the most effective physical components would be prioritized by hierarchical method. Finally, considering the results obtained, not only the principles of native architecture are identified, but also some approaches are introduced to improve the relationship between physical behavior environments in the Niakie neighborhood in Amol.